Organotin(IV) derivatives of o-isobutyl carbonodithioate: Synthesis, spectroscopic characterization, X-ray structure, HOMO/LUMO and in vitro biological activities. (28th January 2016) - Javed, Fatima; Sirajuddin, Muhammad; Ali, Saqib; Khalid, Nasir; Tahir, Muhammad Nawaz; Shah, Naseer Ali; Rasheed, Zahid; Khan, Muhammad Rashid
Graphical abstract: A series of organotin(IV) compounds were synthesized and characterized successfully. The synthesized compounds interact with SS-DNA via the intercalation mode of interaction. Abstract: A series of organotin(IV) complexes have been synthesized by reacting potassium o -isobutyl carbonodithioate with di- and triorganotin halides in methanol under stirring conditions. The newly synthesized complexes have been characterized by elemental analysis, FT-IR, NMR ( 1 H and 13 C) and X-ray crystallography. The FT-IR results show that the ligand acts as bidentate in complexes1 –3 and monodentate in complexes4 and5, which were also confirmed by theoretical calculations. The NMR data reveal four and six coordinated geometries in solution. A HOMO–LUMO study shows that all the complexes are stable. Biological screenings demonstrate that, with a few exceptions, all the complexes show significant activity against various bacterial and fungal strains. The synthesized complexes were also found to be effective antioxidants of the 2, 2-diphenyl-1-picrylhydrazyl radical (DPPH). All the complexes have been assayed for antileishmanial activity in vitro and found some promising results. The UV–Vis studies confirmed that the ligand and its complexes bind to DNA via intercalative interactions, resulting in hypochromism and minor red shifts.